2014
DOI: 10.1016/j.im.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding group maintenance behavior in Free/Libre Open-Source Software projects: The case of Fire and Gaim

Abstract: In this paper we investigate group maintenance behavior in community-based Free/Libre Open Source Software (FLOSS) development teams. Adopting a sociolinguistic perspective, we conceptualize group maintenance behavior as interpersonal communication tactics-specifically, social presence and politeness tactics-that help maintain relationships among group members.Developer email messages were collected from two FLOSS projects with different development status and content-analyzed to identify frequently-used group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…First, the ML NLP might be improved with a richer feature set, though as noted, the performance was already as good as would be expected from an additional human coder. Second, we can consider the effects of additional group maintenance behaviours suggested by Wei et al [19]. The Syracuse SOCQA project has had some success applying ML NLP techniques to these codes, suggesting that this analysis is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, the ML NLP might be improved with a richer feature set, though as noted, the performance was already as good as would be expected from an additional human coder. Second, we can consider the effects of additional group maintenance behaviours suggested by Wei et al [19]. The Syracuse SOCQA project has had some success applying ML NLP techniques to these codes, suggesting that this analysis is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Scialdone et al [18] and Wei et al [19] analyzed group maintenance behaviours used by members to build and maintain reciprocal trust and cooperation in their everyday interaction messages, e.g., through emotional expressions and politeness strategies. Specifically, Scialdone et al [18] found that core members of two teams used more politeness strategies than did peripheral members.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that more than 80% of FLOSS projects fade away due to insufficient long-term participation [10] [12]. "The most common length of participation, across all roles, is no longer than a single month, reflecting a highly skewed distribution of participation", and the tenure of participants varies significantly according to the roles [1].…”
Section: Introductionmentioning
confidence: 99%